THE EFFECT OF WORK TRAINING ON EMPLOYEE WORK PRODUCTIVITY IN THE DEPARTMENT OF VILLAGE COMMUNITY EMPOWERMENT OGAN KOMERING ULU - Sri Sarwo Sari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
Work productivity is basically related to the morale of a person (employees) so it is necessary for the leadership of a government agency to always strive to improve the morale of their employees. If the work productivity of employees increases, it will bring benefits to the institution itself, and on the other hand it can affect the increase in employee work ability. In order to increase the productivity of employees so that they work more actively, the following matters are required: Encouragement of material, money or goods (compensation); the opportunity to gain individual honor, prestige and power; the physical requirements of the desired job are clean, quiet environment or own office space; pride in work, service to family and other people; patriotism, or religious feelings; individual enjoyment and satisfaction in organizational social relationships; conformity with customary practices and usual attitudes and can accept the rules and patterns of behavior of the organization and; feelings participate in most events. Of the several factors that affect employee work productivity, job training and motivation are thought to be very important factors in order to increase employee work productivity at the Ogan Komering Ulu Village Community Empowerment Service. This study aims to determine whether job training jointly affects the work productivity of employees at the Ogan Komering Ulu Village Community Empowerment Service. The results showed that there was a significant influence between job training variables on employee work productivity at the Ogan Komering Ulu Village Community Empowerment Service. The relevant effort is the need to supervise the implementation of employee work, in this case the imposition of strict sanctions against any work violations committed by employees who are often late or absent from work, so that it is expected to increase employee work productivity. Keywords: Training, Work Productivity, Employees